Atlas of Yellowstone - Marcus, W. Andrew; Meacham, James E.; Rodman, Ann Winne, 1958-; Steingisser, Alethea Y., 1970-; Menke, Justin T., 1990-; West, Ross (University of California Press, 2022)
"The second edition of the award-winning Atlas of Yellowstone contains 50% new material, making it the authoritative reference for the world's first national park on its 150th anniversary. The publication of the Atlas of Yellowstone, Second Edition coincides with the 150th anniversary of the founding of Yellowstone National Park--a major international event. The atlas is an accessible, comprehensive guide that presents Yellowstone's story through compelling visualizations rendered by award-winning cartographers from around the world. Readers of this new edition of the Atlas of Yellowstone will explore the contributions of Yellowstone to preserving and understanding natural and cultural landscapes, to informing worldwide conservation practices, and to inspiring national parks around the world while also learning about the many struggles the park faces in carrying out its mission. Ranging from Indigenous Americans and local economies to geysers and wildlife migrations, from the life of one wolf to the threat of wildfires, each page provides leading experts' insights into the complexity and significance of Yellowstone. Key elements of the atlas include: more than 1000 maps, graphics, and photographs contributions from more than 130 experts detailed topographic maps of Yellowstone and Grand Teton National Parks exploration of Yellowstone National Park's influence over 150 years on conservation practice, park management, and American culture new, detailed visualizations of wildlife and carnivore interactions that take advantage of modern GPS technology to track individual animals and entire herds place name origins for Yellowstone and Grand Teton National Parks and the surrounding region"--